Upaya Pemerintah Provinsi Jawa Timur terhadap Program Pemberdayaan Huffadz di Wilayah Kecamatan Senori Tuban - Aya Mamluah (Pendidikan Agama Islam, 2020)
Empowerment becomes an effort to build one's existence in life by encouraging them to have the ability/empowerment. As the provision of resources, opportunities, knowledge and skills, the community increase their capacity to the better future. The empowerment program carried out by Provincial government East Java towards Huffadz Quran is a tribute for their dedication to maintaining Al-Qur'an through memorization. The empowerment is an allowance to them every year. (a). Huffaz empowerment program through the provision of an honorarium. (b). Apart from giving the honorarium, there is a monthly routine program to support the memorization to keep their memorizing in Qur'an, and deepened it with the study of the interpretation of the book Al-Ibriz. Apart from these two things, the Huffadz can practice their Qur'an memorization by holding social activities in the form of donations, especially for orphans.